Piezoelectric, ferroelectric and dielectric characterizations of a new ceramic solid solution (1-x)Ba(Cu1/3Nb2/3)O3-xPbTiO3 with morphotropic phase boundary - Prajapati K.; Singh M.; Singh A.K. (My University, 2025)
The understanding of structure-property co-relations is a key to utilising the materials for their best performances. This paper focuses on the physical property characterization of a new binary solid solution series with formula (1-x)Ba(Cu1/3Nb2/3)O3-xPbTiO3. A unique type of crystal structure evolution as a function of composition has been observed for this solid solution series, where a two-phase coexistence is observed in a very large span of compositions at room temperatures. The microstructure, piezoelectric, ferroelectric and dielectric properties along with their entanglement with crystal structure, have been investigated in detail. The compositional homogeneity of selected compositions has been verified with EDS and XPS. The higher responses in the physical properties have been observed near morphotropic phase boundary compositions. On heating above room temperature, peaks in dielectric permittivity responses have been observed that correspond to the phase transitions of non-centrosymmetric phases. The solid solution's best piezoelectric and ferroelectric responses are observed for the x = 0.70 composition showing higher densification, larger grain size and low dielectric losses, and lies near the morphotropic phase boundary region. The solid solution has enormous potential in piezoelectric industries as it possesses morphotropic phase boundary and high-temperature piezoelectricity. © 2023 Elsevier Masson SAS